Phytochemical analysis & in-vitro cytogenetics assay of chromosomal aberration on peripheral human blood lymphocytes by the leaf crude extract- Passiflora foetida L - V. Pushpa Rani; K. Amila Meera (Zenodo, 2022)
ABSTRACT The present investigation is to evaluate the analysis preliminary photochemical screening and In-vitro cytogenetic assay measuring chromosomal aberration frequencies induced by the leaf crude extract Passiflora foetida L. as an active ingredient in peripheral human blood lymphocyte. Whole blood lymphocytes were cultured in-vitro using a standard protocol and the treatment with the leaf crude extract. The plant extract and fractions revealed preliminary phytochemical compounds with no toxicity. The present investigation revealed that no chromosomal aberration was found in the test sample. And also this study supports, the traditional medicines (herbal extracts) to cure many diseases like diarrhea, intestinal tract, throat, ear infections, fever and skin diseases. The toxicological data are used to evaluate the safety and efficacy of new chemical entities (NCE). One of the most important aspects of safety pharmacology is the evaluation of genotoxicity potential of the NCE. Genotoxicity studies are conducted both at non-clinical and clinical levels. Keywords: Passiflora foetida L., Methanol extracts, Genotoxicity, RPMI-60, Mytomycine C, Chromosomal Aberration. BIBLIOGRAPHY Akiyama H, Fujii K, Yamasaki O, Oono O and Iwatsuki K “Antibacterial action of several tannins against Staphylococcus aureus"J. Antimicrob. Chemother.2001; 48(4): 487–91. Asadujjaman M, Mishuk AU, Hossain MA, Karmakar UK. Medicinal potential of Passiflora foetida L. plant extracts: biological and pharmacological activities. J Integr Med. 2014; 12(2): 121-126. Ashok J. Patil. (2014). Giemsa Banding In Male Rat ( Rattus Rattus ). Biolife. 2(3):842-844. Babu.P. V. A, Liu.D, Gilbert.E.R. (2013). "Recent advances in understanding the anti-diabetic actions of dietary flavonoids" . The Journal of Nutritional Biochemistry 24 (11): 1777–1789. doi : 10.1016/j.jnutbio.2013.06.003 . PMC 3821977 . PMID 24029069 . Balasubramaniam A, Manivannan.R, Baby.E, 2010, Int. J. Drug Formulation Res., 1(II): 144-154. Bandele OJ, Clawson SJ, Osheroff N (2008). ...